HIV case reporting and HIV treatment outcomes in Qatar - Elmoubashar Farag; Ivana Bozicevic; Angham Ibrahim Tartour; Hiba Nasreldin; Joanne Daghfal; Sayed Himatt; Mohamed A. Sallam; Ahmed Ismail; Maha Al Shamali; Peter V. Coyle; Peter V. Coyle; Alaaeldin Abdelmajid; et al. (Frontiers in Public Health, 2023)
AimThe aim of the paper is to provide an overview of available HIV case reporting and treatment data for in Qatar for the period 2015–2020.MethodsHIV case reporting data were analyzed by sex and mode of transmission. To construct HIV care continuum from the data available, we obtained information on the total number of HIV diagnosed patients on antiretroviral treatment (ART) between January 1st 2015 and December 31st 2020, number of patients on ART who had an HIV viral load test and the number who were virally suppressed (defined as having the viral load of less than 1,000 copies/mL).ResultsA total of 515 HIV cases were reported to the Ministry of Public Health since beginning of reporting in 1986, and that included Qatari nationals and expatriate residents diagnosed in Qatar. There was an increase in the annual number of newly reported HIV cases from 16 cases in 2015 (of these, 14 were males) to 58 cases in 2020 (of these, 54 were males). The total number of HIV diagnosed people on ART increased from 99 in 2015 to 213 in 2020. During 2020 the overall viral load testing coverage and viral load suppression among those tested for viral load in men were 72.5% and 93.1%, respectively, while in women these values were 60.4% and 84.4%, respectively.ConclusionDue to increase in newly reported HIV cases, there is a need to develop an effective HIV strategic information system in Qatar and data-driven and targeted national HIV response.